Innovation in Entrepreneurship and Its Role in Promoting Sustainable Economic Growth - Sugiarti, Rita; Elmiwati, Elmiwati (Journal of Comprehensive Science, 2024)
This research explores the role of entrepreneurial innovation in supporting sustainable economic growth by using a questionnaire that has been tested for validity and reliability. The validity test results show that all 16 items have a correlation coefficient above 0.60, while the reliability test using Cronbach's Alpha yields a value of 0.9, indicating high consistency of the research instrument. Descriptive statistical analysis from 25 respondents shows a positive view towards innovation, with average responses ranging from 3.2 to 4.5 and a median of 4.0. This research also compares the results with three previous studies: by Fajri (2021), Bhegawati et al. (2022), and Santhi & Affandi (2020), which assert that entrepreneurial innovation not only contributes to improving the financial performance of SMEs but also serves as a driving force for economic growth through job creation and productivity enhancement. These findings highlight the importance of innovation in creating a sustainable and mutually beneficial entrepreneurial ecosystem. Therefore, focusing on innovation in entrepreneurship is essential to achieve sustainable economic growth, demonstrating a close relationship between innovation and its positive impact on the economy as a whole. This study provides important insights for SMEs and policymakers in developing strategies that support innovation for better economic growth.